A Catalogue of Indian Hydrophiloidea (Insecta: Coleoptera) - Gupta, Devanshu; Sonali, Shipra; Ghosh, Sujit Kumar; Das, Priyanka; Jaiswal, Deepa; Chandra, Kailash (Zootaxa, 2024)
This catalogue lists 286 valid species included in 49 genera and six families of the superfamily Hydrophiloidea (Coleoptera), recorded from India. The family Helophoridae accommodates eight species (one genus), Epimetopidae five species (one genus), Georissidae seven species (one genus), Hydrochidae four species (one genus), Spercheidae two species (one genus), and Hydrophilidae 260 species (44 genera). Of these, 113 species are apparently endemic to India. We include synonyms, type localities, and distribution of the species in Indian states and biogeographic zones including localities where known. The Himalayan region supports the maximum diversity of hydrophiloids (140 species), followed by the Deccan Peninsula (96 species), Western Ghats (84 species), Gangetic Plains (84 species), Northeast (74 species), Semi–Arid (34 species), Islands (26 species), and Desert (10 species).